The utility of long-term blood pressure variability for cardiovascular risk prediction in primary care - Stevens, S; McManus, R; Stevens, R (Lippincott, Williams & Wilkins, 2018)
Objectives: Blood pressure is a long-established risk factor for cardiovascular disease. Systolic blood pressure is used in all widely-used cardiovascular risk scores for clinical decision-making. Recently, within-person blood pressure variability has been shown to be a major predictor of cardiovascular disease. We investigated whether cardiovascular risk scores could be improved by incorporating blood pressure variability with standard risk factors. Methods: We used cohort data on patients aged 40 to 74 on 1/1/2005, from English general practices contributing to the Clinical Practice Research Datalink, a research database derived from electronic health records. Data were linked to hospital episodes and mortality data. Systolic blood pressure variability independent of the mean was calculated across up to 6 clinic visits. We divided data geographically into derivation and validation datasets. In the derivation dataset we developed a reference model, incorporating risk factors used in previous scores and an index model, incorporating the same factors plus blood pressure variability. We calculated model validation statistics in the validation dataset including calibration ratio and c-statistic. Results: In the derivation dataset, blood pressure variability was associated with cardiovascular disease, independently of other risk factors (p=0.005). However, in the validation dataset, both models had similar c-statistic (0.7415 and 0.7419 respectively), R2 (31.8 and 32.0 respectively) and calibration ratio (0.938 and 0.940 respectively). Conclusions: The association of blood pressure variability with cardiovascular disease is statistically significant in a large dataset but does not substantially improve the performance of a cardiovascular risk score.